JUSTIFICATION OF THERAPEUTIC EFFICACY OF DENDRITIC CELLS DERIVED FROM CRYOPRESERVED PRECURSORS IN AN ADJUVANT ARTHRITIS MODEL - Goltsev, A.M.; Kisielova, H.H. (World of Medicine and Biology, 2023)
Tolerogenic dendritic cells are of particular interest in the search for new approaches to the correction of the T regulatory immunity circuit in the treatment of autoimmune diseases. The aim of this study was to investigate the efficacy of dendritic cells derived from cryopreserved bone marrow mononuclear cells in the formation of a tolerogenic platform in the recipient through the mechanism of stimulating T regulatory cells in an experimental model of adjuvant arthritis. Dendritic cells were obtained in vitro from cryopreserved mononuclear cells. On the 14th day of pathology development, various types of tolerogenic dendritic cells were administered to the animals; the content of T regulatory cells (CD4+CD25+ and FOXP3+) and the level of foxp3 gene expression in the recipient's spleen cells were evaluated. The developed method of cryopreservation of mononuclear cells, based on theoretical justification, provided high tolerogenic activity of dendritic cells derived from cryopreserved precursors. As a result, there was an increase in the content of T regulatory cells and their functional potential through the activation of the foxp3 gene. This led to the normalization of the main clinical diagnostic indicator – the arthritis index.
Keywords: cryopreservation of bone marrow mononuclear cells; tolerogenic dendritic cells; T regulatory cells; foxp3 gene; adjuvant arthritis